The author writes back (and speaks up) - Hart, Jonathan (Primerjalna književnost, 2008)
The author speaks and writes back against his or her metaphorical death. Aristotle's Poetics is helpful for this context when it discusses the effect that the poet's plot and character have on the audience. Literary and non-literary texts involve a dramatic engagement between author and audience.
Keywords: poetika; retorika; rhetoric; Aristoteles; pisatelj; writer; bralec; anagnorisis; katarza